Problems and Dynamics of Thought of Da'wah Institutions: Between Islamization and Secularization - Al Kahfi, Al Kahfi; Firdaus, Muhammad; Yaqub, M. (PT. Student Rihlah Indonesia, 2025)
This study is important in understanding how these institutions respond to the ideological tension between two major currents: Islamization and secularization, both of which significantly influence policy direction and da’wah strategies. The main objective of this research is to explore the evolving thought dynamics within contemporary da’wah institutions and their impact on institutional management and social outreach. Using a library research method, the study examines classical and contemporary literature on secularization, Islamization, and institutional da’wah management. The findings reveal that Islamization-oriented institutions emphasize religious identity and the formal application of sharia, whereas institutions leaning towards functional secularization prioritize universal values, inclusive language, and context-sensitive strategies for multicultural societies. The novelty of this study lies in its comparative analysis that highlights how different ideological orientations shape organizational design, leadership models, and public communication strategies. The implications suggest that integrating Islamic values with inclusive and adaptive modern management principles is essential for policy development in contemporary da’wah institutions.